PERENCANAAN STRATEGIS SISTEM INFORMASI PENJUALAN PADA PT TEXFORMA TEKNOLOGI INDONESIA MENGGUNAKAN METODE WARD & PEPPARD - Fikry Alghifari (Jurnal Teknologi Informasi, 2022)
PT Texforma Teknologi Indonesia is a company that has grown to become one of the partners and assists in textile automation, providing textile machines that are integrated with industry 4.0, ERP systems, accessories and spare parts. However, there are several problems with the company, namely the sales information system that is still manual resulting in the slow duration of doing the tasks that have been given due to the lack of a system. This study aims to make strategic planning of information systems so that the company can run its vision, mission and goals. In this study the authors used the Ward and Peppard method. The results of this study produce recommendations for companies in the form of system designs that aim to make it easier for companies to carry out their business activities and be able to compete with other companies.